Analysis of Implementation of FACTS Devices in Power Factor Improvement (International Journal of Engineering and Computer Science, 2018)
This paper presents an analysis of implementation of Flexible AC Transmission System (FACTS) devices for maintaining Power Factor. The electrical loads include induction motor driven equipments, which consume reactive power, increase the amount of apparent power in the distribution system, which is important because a low power factor can waste energy, and results in inefficient use of electrical power and often result in higher energy bills. The improvement of Power Factor as close as unity is very essential in the industry as well as domestic electric appliances, due to increase in power demand. The Power factor maintenance provides increase in system efficiency.  The solution for power factor unity is done with FACTS devices, which has the manageable capacity. The possibility of low power factor increases with inductive load in nature. Hence, the need of unity in power factor is very significant.